KARAKTER PUNAKAWAN SEBAGAI STICKER CHAT DALAM KAMPANYE PENANGGULANGAN COVID-19 DI SURAKARTA - Ipung Kurniawan Yunianto (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2021)
Punakawan, a wayang purwa character whose presence is always awaited, because of his humor in conveying moral messages and social issues that are hotly discussed by the community. They are able to communicate messages according to trends, adaptive to situations and conditions, as well as communicative, so that they are easily accepted by the audience. Starting from the elders who enjoy pakeliran to the Post-Millennial generation who are enthusiastic about social media. This design study is a way of optimizing the achievement of the message of the Covid-19 pandemic response campaign in Surakarta, which is applied to social media in the form of digital stickers on the instant messaging platform for the Post-Millennial generation group in Surakarta. Punakawan as a visual communication strategy with cultural insights in the midst of a pandemic situation, is adjusted to post-millennial visual references, so that messages are easy to remember, effective, and well conveyed. This design study will design instant messaging chat stickers for the millennial generation as a campaign for handling Covid-19 in the city of Surakarta, so that qualitative ethnographic methods are carried out, with the stages of gathering information in the city of Surakarta aimed at the post-millennial generation group in the form of observation, interviews, and problem identification. , the planning stage by determining the main ideas through analysis, integration, abstraction, using a visual rhetorical approach, synthesis and selection stages, then the following realization of prototype trials, and implementation of digital stickers on communication technology 4.0 on Google Paly Store as monetizing. Keywords: Covid-19 pandemic, sticker, Punakawan